Nutrient uptake efficiency in controlled-release, compound and straight fertilizers - Low, Wei Han.
Due to the escalating cost of fertilizer, farmers need to use fertilizer more efficiently in order to minimize the wastage and also hazards to the environment. Controlled-release fertilizers have been reported to increase nutrient availability in the plant-soil system and reduces nutrients lost from leaching and surface runoff. The objectives of this study were (i) to determine the efficiency of controlled-release fertilizer (KAMILA), compound fertilizer (F1), and straight fertilizer (Ammonium Sulphate, Phosphate Rock, and Muriate of Potash) on the growth of Napier grass (Pennisetum purpureum), and (ii) to identify the effectiveness of each fertilizer for increasing plant growth. This study was conducted at the glasshouse 2D, Field 2, UPM. Randomize complete block design (RCBD) was used in this experiment using 3 types of fertilizer (CRF, FI, SF) and 4 rates (0g, 30g, 45g, and 60g) with 5 replications. Plant top was harvested at the first, second, third and fourth month after fertilizer application. Overall, the results showed that the used of controlled-release fertilizer enhanced the plant total dry matter yield and increased the nutrient uptake efficiency of N, P and K when compared to the compound and straight fertilizers. The use of controlled-release fertilizer was able to save approximately 35% of applied fertilizer in contrast to other conventional fertilizers to give the same plant dry matter yield. Therefore, a substantial amount of fertilizer can be reduced by adopting controlled-release fertilizer instead of conventional fertilizers. Further study need to be carried out on the larger scale experiment on the oil palm plantation to ascertain the accurate amount of cost saving from the use of Malaysian made controlled-release fertilizer.